'Who Bravely Fights, and Like Achilles Bleeds': The Ideal of the Front‐Line Soldier during the Long Eighteenth Century. (19th August 2019) - Taylor, Jonathan
Abstract: Augmenting recent efforts to recover a broader spectrum of eighteenth‐century attitudes towards martial models of masculinity, this article challenges traditional arguments that eighteenth‐century Britain either rejected or softened martial ideals by examining the period's under‐explored veneration of the sanguinary front‐line soldier. Connecting examples from literature and material culture, it demonstrates that eighteenth‐century artists valorised Achilles, literature's most bloodthirsty hero, as the archetype for this battlefield figure and made anachronistic comparisons with Homer's hero the subject of numerous encomiums on successive eighteenth‐century leaders. The conclusion outlines the persistence of this British cult of Achilles from the nineteenth century to the twenty‐first.